Expanding Women’s Access to The Banking Sector: Analysis of Perceptions, Behavior, Culture, and Social Class of Female Customers Towards The Effectiveness of Working Capital Financing at Islamic Banking in Palembang - Maftusolikhah, Maftusolikhah; Siti Mardiyah; Erdah Litriani; Sri Delasmi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
The increase in micro, small, and medium enterprise (UMKM) units managed by women has contributed a positive impact on reducing poverty rates. The data highlighting lack of female entrepreneurs of UMKM who used and/or are supported with financing facility from banks have led to some emerging questions to be discussed. This present study promotes significance, namely: 1) The effectiveness of financing tends to affect the banks’ performance through created demands; 2) The results of this study are expected to enhance the attention of Islamic banking to female customers by increasing the allocation of financing for those customers; 3) The further implication of these findings is the increase in national economic growth from the UMKM actuated by women; 4) The broader implication is the reduction of working women at high risks because of the conducive business climate in Indonesia with the support of the banking sector. Therefore, this quantitative research that was conducted with regression analysis focused on the internal factors to analyze perceptions, behavior, culture and social class of female customers towards the effectiveness of working capital financing at Islamic banking in Palembang. The findings revealed that the variable of perceptions gave a positive effect on the effectiveness of financing of 0.316, behavior showed a positive impact on the effectiveness of financing of 0.676, culture noted a positive influence on the effectiveness of financing of 0.346, whereas social class demonstrated a negative impact on the effectiveness of the financing of −0.14.